ASSESSING THE SPATIAL ASPECTS OF ECO-TOURISM DEVELOPMENT IN BUKIT LAWANG AREA - Liyushiana, Liyushiana; Sinaga, Jastrid Caroline Herera; Ismail, Muhammad; Denny, Agustinus (Politeknik Pariwisata NHI Bandung, 2023)
Bukit Lawang is part of the conservation area of Gunung Leuser National Park (TNGL) and is a popular tourist destination in Langkat Regency. The attraction of Bukit Lawang has resulted in the concept of ecotourism, with the hope that tourist activities will have a friendly impact on the natural ecosystem. Therefore, it is necessary to evaluate the influence of ecotourism activities within the scope of the 3A-based tourism concept and the spatial aspects of Google Earth imagery using time series techniques from 2012-2022. It is evident that from the 3A perspective, there has been a change in the needs of tourists for new tour packages that still prioritize nature tourism, the addition of alternative road sections as a form of accessibility development to Bukit Lawang, and the addition of accommodations to meet tourists' needs. From satellite imagery, there is an expansion of settlement areas, lodgings, parking areas, and a bridge access to a new lodging area within the range of 2012-2022.